EFFECTS OF TRANSFORMATIONAL LEADERSHIP STYLE ON THE WORKING ENVIRONMENT OF SCHOOLS - Muhammad Mukhtyar; Nisar Ahmad; Dr. Khatiba bibi (International Journal of Contemporary Issues in Social Sciences, 2024)
A transformational leadership style has gained significant attention from leaders. The major aim of the study was to explore the key aspects of the transformational leadership style and their effect on the working environment of schools. The study is quantitative. Primary data from 401 teachers was collected using a convenient sampling technique through web surveys. SPSS version 26 was applied to analyze data, and regression analysis was conducted to find the effect of transformational leadership style on the working environment. A highly significant positive effect of the transformational leadership style on the working environment of schools was found. It is recommended that heads of schools should consider transformational leadership style during their decision-making to improve the school outcome.